DEVELOPING AN ENGLISH WRITING MATERIALS MODELS BASED ON SMART APPLICATION CREATOR FOR JUNIOR HIGH SCHOOL STUDENTS - Rya Gita Sari; Audi Yundayani; Didik Santoso (SOSCIED, 2023)
The student’s need for English writing materials that can improve the student’s writing skills to make the learning process more interesting, challenging, an interactive. This study aims to develop English writing materials models based on SAC for junior high school. The objectives of this study were:(1) To know the students needs for English writing materials in junior high school,(2) To know how to design the English writing materials based on SAC for junior high school, (3) To know the development of English writing materials based on SAC for junior high school,(4) To know the implementation of English writing materials based on SAC grade I,(5) To know the effectiveness of English writing materials models based on SAC for teaching the students. This research uses the ADDIE model approach which has five steps. It determine the efficacy of English writing materials based on SAC in the learning. This research uses research & development ( R&D ) study. The subjects of the study were the students in the ninth grade of SMP Negeri 2 Tanjung Pura. The instruments for collecting data were questionnaires, interview, and English test. This writing materials uses a contextual teaching materials (CTL) approach to improve the student’s writing skills. The final result show that the average result of content expert’s score is 89%. The average result of media expert score is 87%. The average result of student;s response score is 85,9%. The average result of teacher response score is 88,3%. There are differences in test result before and after the developing English writing materials based on SAC. The average post test is higher. There is a significant improvement in student’s writing skills after they were taught using writing materials based on SAC. It can be concluded that developing English writing materials based on SAC is effective in increasing student’s writing skills in learning